The Export Determinants of Indonesian Cut Flower in The International Market - Niza Arumta; Jangkung Handoyo Mulyo; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2019)
Trade statistics of Indonesian cut flower indicates the potential of Indonesia as an exporting country. The international market becomes more attractive as the increasing trend of demand and the rising cost for producing cut flowers shows the various challenges for emerging countries. This study investigates whether the analytical gravity model fixed effect, common effect or random effect model is proper and what determinants have significant effects to the exports of Indonesian cut flower to partner countries. The data encompasses the period of 2008 to 2017 as the series data and the seven destination export countries from Indonesia as the cross-sectional data, using the panel regression with the basic gravity model. The estimation results show the fixed effects model is the proper model to explain the determinants of bilateral export on cut flower. The estimates imply the corroborate signs with GDP per capita of Indonesia, GDP per capita of partner countries and exchange rate while those variables with the opposite sign are distance and trade openness. Thus, the export promotion, quality improvement and technology development are required in the development of export of cut flower industries.